Cultivating Patriotism: Independent Curriculum and Strengthening Pancasila Profile (P5) in Kindergarten - Citra, Aliva; Syaodih, Ernawulan; Rachmawati, Yeni; Solahudin, M. Nizan; Morrison, Richard (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
This research aims to understand the presence of the independent curriculum in early childhood education with a specific focus on the correlation between this curriculum and the locally infused P5 program. The study formulates research objectives centered on planning P5 programs themed around local wisdom, implementing these programs, and evaluating their effectiveness. Employing a qualitative approach with a descriptive method, data collection methods include observation, interviews, and documentation. The research findings emphasize the essential role of the P5 program within the independent curriculum. This program successfully enriches students' knowledge and understanding of local wisdom, suggesting a need for further integration of local wisdom elements into the independent curriculum at the early childhood education level. It is crucial to enhance parental involvement in the implementation of the P5 program. Additionally, developing more holistic evaluation strategies is recommended to measure the long-term impact of the independent curriculum and the P5 program on the overall development of students.┬á┬á